Abnormalities of the muscles of the soft palate and their impact on auditory function in patients operated on for cleft palate: a case-control study. Issue 6 (July 2019) - Arunachalam, D.; Pendem, S.; Ravi, P.; Raja V.B., K.K.
Abstract: Patients with cleft palate have a high incidence of otitis media (OM), which, even after palatal repair, can persist and lead to auditory dysfunction. We aimed to identify what predisposes such patients to develop OM and correlate it with auditory function. We designed a prospective case-control study of adults who had had their cleft palates repaired in childhood. We examined the anatomy of the eustachian tube and the paratubal muscles of the soft palate with magnetic resonance imaging (MRI), assessed auditory function, and correlated the results to evaluate the impact of the pathological anatomy on the function of the middle ear. A total of 64 ears in 32 patients were evaluated (Group A, n = 16) (Group B, controls = 16). MRI showed a short eustachian tube with a shortened tensor attachment in Group A when compared with Group B. The pterygoid hamulus was found to be intact in both groups, but extensive perihamular fibrosis was seen in Group A. A total of 15 ears in Group A had loss of hearing (prevalence ratio (PR) 1.08), (13 mild loss, and 2 moderate loss), and impedance audiometry showed effusion of the middle ear in 12 ears in 16 patients, and dysfunction of the eustachian tube with high negative pressure in the middle ear in four ears in the 16 patients (PR 4.6). These could be positively correlated with the pathological anatomy using Pearson's correlation coefficient. Otitis media is persistent and can lead to conductive hearing loss in adults who have been operated on for cleft palate. This can be attributed to abnormalities in the development of the eustachian tube and the paratubal musculature.